The role of a national payment service provider in case of implementation budget and tax and monetary policy - S. V. Krivoruchko (Путеводитель предпринимателя)
The author analyzes a role of a national payment service provider in case of implementation of measures of coordination of activities of the Government and Bank of Russia within budget and tax and monetary policy, and allocates systemically the significant payment service providers of the Bank of Russia and NPO of CJSC National Settlement Depositary which are key infrastructures in this process.